Perceived behavioral control as a potential precursor of walking three times a week: Patient’s perspectives - Busse Cárdenas, Peter (2018)
Background: Behavior change theories can identify people’s main motivations to engage in recommended health practices and thus provide better tools to design interventions, particularly human centered design interventions. Objectives: This study had two objectives: (a) to identify salient beliefs about walking three times a week for 30 minutes nonstop among patients with hypertension in a low-resource setting and, (b) to measure the relationships among intentions, attitudes, perceived social pressure and perceived behavioral control about this behavior. Methods: Face-to-face interviews with 34 people living with hypertension were conducted in September-October 2011 in Lima, Peru, and data analysis was performed in 2015. The Reasoned: Action Approach was used to study the people’s decisions to walk. We elicited people’s salient beliefs and measured the theoretical constructs associated with this behavior. Results: Results pointed at salient key behavioral, normative and control beliefs. In particular, perceived behavioral control appeared as an important determinant of walking and a small set of control beliefs were identified as potential targets of health communication campaigns, including (not) having someone to walk with, having work or responsibilities, or having no time. Conclusions: This theory-based study with a focus on end-users provides elements to inform the design of an intervention that would motivate people living with hypertension to walk on a regular basis in low-resource settings.